A Chocó Indian in Hillsboro, Kansas (2022)
eng: Antecedents During 1956, 1958, and 1959 I was engaged in language research and Bible translation work with the Choco Indians living in the Darien province of southern Panama. The work was conducted on the field in the Choco setting so I could learn to appreciate the Choco culture and world view. During the 1958 and 1959 assignments I made acquaintance with Aureliano (Hombria) Sabugara, a Choco Indian, living on the Jaque river close to the Panama-Colombia border. Aureliano had initially heard the Word of God when the Rev. Glenn Prunty of the New Tribes Mission read to the Indians a series of Bible stories. These Bible stories had first been translated into a Colombian Choco dialect, and subsequently they had been "desk edited" for the Choco dialect spoken in Panama on the basis of my 1956 field notes. Aureliano was one of several scores of Indians who in response to this good news “gave God the hand" and then began “to walk on God's road."